1995
DOI: 10.1111/j.1600-0447.1995.tb09545.x
|View full text |Cite
|
Sign up to set email alerts
|

Lithium prophylaxis of manic‐depressive disorder: daily lithium dosing schedule versus every second day

Abstract: The prophylactic efficacy of lithium carbonate given every second day versus daily intake was compared in a double-blind study including 50 manic-depressive patients. The patients met the DSM-III-R criteria for bipolar disorder or depressive disorder; according to ICD-8 the patients fulfilled criteria for manic-depressive disorder: All patients had experienced at least 3 episodes of mania or major depression, and all had been euthymic for at least 4 months. The median doses of lithium carbonate given were 800 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1

Year Published

1995
1995
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(24 citation statements)
references
References 14 publications
2
21
1
Order By: Relevance
“…However, alternate-day dosing was found in one study to be less effective than SDD. 31 Many patients receiving lithium have other risk factors for renal disease, including nephrotoxic medications, age, comorbidities, long duration of lithium therapy, and possibly a prior history of lithium toxicity. 2 Although the exact degree of renal toxicity or optimal dosing regimen are not definitively known, there is evidence for a possible association between renal impairment and lithium therapy; therefore, prescribers should do their utmost to mitigate this potential risk by ensuring the lowest effective lithium dose is used, individualizing dosing regimens to minimize adverse effects, and regularly monitoring renal function and lithium serum levels to prevent episodes of toxicity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, alternate-day dosing was found in one study to be less effective than SDD. 31 Many patients receiving lithium have other risk factors for renal disease, including nephrotoxic medications, age, comorbidities, long duration of lithium therapy, and possibly a prior history of lithium toxicity. 2 Although the exact degree of renal toxicity or optimal dosing regimen are not definitively known, there is evidence for a possible association between renal impairment and lithium therapy; therefore, prescribers should do their utmost to mitigate this potential risk by ensuring the lowest effective lithium dose is used, individualizing dosing regimens to minimize adverse effects, and regularly monitoring renal function and lithium serum levels to prevent episodes of toxicity.…”
Section: Discussionmentioning
confidence: 99%
“…31,32 Fifty patients treated with lithium were randomized to either remain on SDD, or receive lithium every second day alternating with placebo. No significant difference was found between groups regarding adverse effects; however, authors noted a trend toward reduced polyuria and polydipsia and less diarrhea in the alternate-day group.…”
Section: Alternate-day Dosingmentioning
confidence: 99%
“…according to the DSM-IV [30] . Euthymia was established as not having met DSM-IV criteria for any mood episode (a score ^ 9 on the BechRafaelsen Mania Scale [31] , and HAMD scores between 0 and 7 [32] 11 months, respectively. All subjects were evaluated by a semi-structured questionnaire.…”
Section: Subjectsmentioning
confidence: 99%
“…In a study comparing daily lithium dosing versus lithium dosing every second day, Jensen et al [9] showed that daily lithium dosing was clinically superior and that TSH levels in this group of patients were significantly highest.…”
Section: Discussionmentioning
confidence: 99%